Mesenchymal stem cell-derived exosomes in myocardial infarction repair: therapeutic potential and scaffold-based delivery strategies - Azimian Zavareh, Vajiheh; Eslampoor, Negar; Panahi-Alanagh, Sanaz; Malekmohammad, Latifeh; Stanek, Agata (Frontiers in Pharmacology, 2026)
Myocardial infarction (MI) remains a leading cause of global mortality, with current therapeutic modalities offering limited capacity for complete myocardial tissue regeneration. Advances in regenerative medicine have introduced stem cell-based approaches, among which mesenchymal stem cells (MSCs) have garnered significant scientific curiosity due to their multipotent differentiation potential and favorable safety profile. However, evidence suggests that the primary therapeutic effects of MSCs are mediated through their paracrine secretion of bioactive factors, notably exosomes. These MSC-derived exosomes (MSC-Exos) can modulate key aspects of cardiac repair, such as enhancing angiogenesis, preventing apoptosis, and alleviating inflammation by transferring genetic material such as miRNAs, proteins, and lipids and by activating molecular pathways critical to cardiac repair. Numerous studies as well as preclinical and clinical trials are currently investigating MSC-Exos for tissue regeneration. This review critically examines the biological characteristics and underlying mechanisms of MSC-Exos in myocardial repair, with particular focus on cell sources such as bone marrow-derived MSCs (BMMSCs), adipose-derived MSCs (ADSCs), and human umbilical cord MSCs (HUCMSCs), and evaluates their roles from multiple perspectives. Moreover, this review emphasizes innovative delivery approaches, including hydrogel-based systems, aimed at maximizing therapeutic effectiveness and accelerating translational potential. The integration of scaffold technologies and exosome engineering holds substantial promise for translating this cell-free approach into effective clinical treatments, presenting MSC-Exos as a transformative strategy with the potential to markedly improve outcomes in MI.